Comments on the substitute texts of bills 3580 and 3633 proposing to amend law no. 30001, law on economic and social reintegration for returned migrants - Malapi Hernández, Daniela (2023)
This article comments on the relevance of the substitute texts of Bills 3580 and 3633. Hence, it explores the background of the legislation on incentives for returned migrants, as well as the scope and amendments of Law 30001. It also provides recommendations aimed at improving the National Migration Policy, whose approach should encourage the return of human talent residing abroad.